PENGARUH MODAL DAN LUAS LAHAN TERHADAP TINGKAT PENDAPATAN PETANI PADI (Studi Kasus Petani Padi Di Kecamatan Aralle Kabupaten Mamasa) - Fajariani, Nur; Kamarudin, Jamaludin; Suarno, Suarno (LPPM Universitas Muhammadiyah Mamuju, 2022)
Rice farmers are actors who carry out farming on paddy fields which are managed based on physical, biological and socio-economic environmental capabilities in accordance with their goals, abilities and resources to produce rice for the daily basic needs of the people of Aralle District, Mamasa Regency. This study aims to determine the effect of capital and land area on the income level of rice farmers in Aralle District, Mamasa Regency and to analyze the most dominant variable influencing the income level of rice farmers in Aralle District, Mamasa Regency. The variables used in this research are capital factor (X1), land area factor (X2), and income level (Y). The method used in this research is using the accidental sampling method by distributing questionnaires to 100 rice farmer respondents in Aralle District, Mamasa Regency. The analysis technique used is multiple linear regression analysis to measure the effect partially and simultaneously. The results obtained show that the capital variable has a significant effect on the income level of rice farmers in Aralle District, Mamasa Regency and the variable land area has a significant effect on the income level of rice farmers in Aralle District, Mamasa Regency. While the factor of land area that most dominantly influences the level of income of rice farmers in Aralle District, Mamasa Regency, because from the results of multiple linear regression analysis the beta value obtained is the highest at 2,380 with the lowest significant value, namely 0.000.